The Determinants of Debt Ownership Structure - Some Empirical Evidence - Deo, Malabika; Jackline, S. (Indian Journal of Finance, 2009)
The determinants of debt structure have captured academic thought for many decades. If optimal debt structures do exist and that these structures maximize firm's value, obtaining an understanding of the determinants of debt structure is important in obtaining an understanding of the way firms maximize value. Decisions about debt structure may have important implications as regards to shareholder wealth effects. Therefore, understanding of the determinants of debt structure is of interest to academics, politicians, shareholders and financiers. This paper presents an empirical investigation of the factors determining debt structure of Indian Companies.